EVALUASI TATA KELOLA SISTEM INFORMASI AKADEMIK MAHASISWA UNIVERSITAS NUSANTARA PGRI KEDIRI - Candra Ratna Hariyanti; Bambang Soedijono WA; Sudarmawan Sudarmawan (Universitas Janabadra, 2020)
Higher education is an organization that requires information technology and adequate information systems so that its objectives can be achieved. An institute that applies information technology is expected to conduct an evaluation of information technology currently in use to help measure how well information technology governance is implemented. One of framework for evaluating governance is COBIT 4.1. This research focuses on the domain of monitoring and evaluating(ME) to evaluate the governance of student academic information systems at Nusantara University PGRI Kediri. COBIT 4.1 was chosen because it suits the educational context and can identify information technology resources (systems, people, data and technology). Data collection techniques are done by interview and questionnaire. The results of the study are the value of the level of maturity in the governance of SIAKAD in ME domain and the proposed improvement of governance. Based on the calculation of governance maturity level that is on average is at level two where the campus has been able to make planning and management of computer-based systems but there is no formal documentation.Keywords: Cobit 4.1, Monitoring and Evaluation, IT Governance